2019
DOI: 10.1002/mds.27821
|View full text |Cite
|
Sign up to set email alerts
|

Tremor habituation to deep brain stimulation: Underlying mechanisms and solutions

Abstract: DBS of the ventral intermediate nucleus is an extremely effective treatment for essential tremor, although a waning benefit is observed after a variable time in a variable proportion of patients (ranging from 0% to 73%), a concept historically defined as “tolerance.” Tolerance is currently an established concept in the medical community, although there is debate on its real existence. In fact, very few publications have actually addressed the problem, thus making tolerance a typical example of science based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 135 publications
0
78
0
Order By: Relevance
“…Recent studies have revealed that long‐term VIM‐DBS may induce waning benefits (tremor habituation to DBS) and delayed onset of gait ataxia in ET 9,10 . Shih et al 11 reported 73% experienced waning benefit in patients with ET who underwent VIM‐DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that long‐term VIM‐DBS may induce waning benefits (tremor habituation to DBS) and delayed onset of gait ataxia in ET 9,10 . Shih et al 11 reported 73% experienced waning benefit in patients with ET who underwent VIM‐DBS.…”
Section: Discussionmentioning
confidence: 99%
“…While VIM-DBS is a safe and effective therapy for patients with severe refractory ET, up to 40-70% of patients will experience worsening of tremor over time [10,11]. Potential causative factors include disease progression, dis-ruption of oscillatory neuronal pathways, side effects from long-term stimulation, changes in impedance, tolerance, or a combination thereof [2, [12][13][14]. Stimulation of structures closer to the midline such as the thalamus and STN, can manifest ipsilateral benefits and side effects.…”
Section: Other Potential Factors Affecting Long-term Dbs Efficacy Andmentioning
confidence: 99%
“…One strategy has been the reduction of current density by reducing PW or the amplitude of stimulation. After discovering the threshold for stimulation-induced cerebellar tremor or ataxia, the frequency and amplitudes can be slowly incremented until the tremor is controlled or intolerable adverse effects manifest [14]. The advent of directional DBS may possibly address these stimulationinduced side effects, which may potentially be avoided by delivering stimulation in an axially asymmetric fashion, away from unintended tracts.…”
Section: Management Of Changes In Clinical Effectiveness and Thresholmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term safety and efficacy of DBS are well-established [3], although it is not certain whether its initially reported superior tremor suppression is also achieved in successive cohorts [4]. Additionally, evidence shows that 33 out of 45 patients in one study (73.3%) reported waning tremor control at a mean time of 18.8 ± 15.1 months postoperatively [5].…”
Section: Introductionmentioning
confidence: 99%